PLANKTON - Wood, John, 1990-; Holmes, Kirsty; Li, Amy (King's Lynn : BookLife Publishing, 2018)
What would the world be like without plankton? And why are plankton important to you? Learn about plankton and their place on our planet.
t The last blue whale -- t Worried doctors and sick people -- t Cloud control -- t Saving the plankton.
Includes index
Keywords: Plankton -- Juvenile literature; Plankton; Juvenile works; Juvenile literature